E Eksistensi Penganut Hindu Kaharingan Dalam Menjaga Kerukunan Umat Beragama di Kota Palangka Raya - Susi Susi (Satya Widya: Jurnal Studi Agama, 2021)
The development of religious harmony is a tool to unite the nation in pluralist and pluralistic social conditions. The outline of the population of Palangka Raya City consists of various ethnicities, religions, races, between groups living side by side in an area in harmony and participating in upholding tolerance between people. The importance of maintaining harmony in a pluralistic society so that every element of society needs to play an active role in managing and realizing peaceful, harmonious and harmonious living conditions. The existence of Hindu Kaharingan adherents in Palangka Raya City, takes part in maintaining religious harmony in Palangka Raya City as a form of responsiveness in facing critical problems of a pluralistic society. Conflicts that arise due to societal differentiation can occur at any time. Therefore, the implementation of harmony in life by practicing the trilogy of religious harmony is a strategy carried out in order to create a sense of unity in the people of Palangka Raya City, which is increasingly dynamic with the times.